2017
DOI: 10.1002/hed.24785
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal scapular artery as a recipient vessel in the vessel‐depleted neck during free tissue transfer in head and neck reconstruction

Abstract: The dorsal scapular artery is a viable recipient vessel during head and neck reconstruction in the vessel-depleted neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…23 In these cases, other arteries must be considered, such as the facial, transverse cervical, internal mammary, and dorsal scapular arteries. 52,53 There are many factors to consider when deciding on recipient vessels, including vascular pedicle length, caliber, flow, treatment effects and pedicle geometry. The reconstructing surgeon should be cognizant, however, of the potential effects of using the superior thyroid artery on thyroid function and should monitor this post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…23 In these cases, other arteries must be considered, such as the facial, transverse cervical, internal mammary, and dorsal scapular arteries. 52,53 There are many factors to consider when deciding on recipient vessels, including vascular pedicle length, caliber, flow, treatment effects and pedicle geometry. The reconstructing surgeon should be cognizant, however, of the potential effects of using the superior thyroid artery on thyroid function and should monitor this post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Vieira et al [62] also reported a case in which a vastus lateralis free flap was utilized for clival reconstruction due to osteoradionecrosis secondary to proton beam therapy. Another approach using the transmaxillary corridor to tunnel the pedicle across the face in the maxillary subcutaneous tissue for contralateral facial vessel anastomosis has also been described [63] .…”
Section: Free Microvascular Tissue Transfersmentioning
confidence: 99%
“…Recipient vessels outside of the reconstruction zone have also been proposed. The dorsal scapular artery (Rosko et al, 2017), internal mammary vessels (Schneider et al, 2012), internal mammary artery perforators (Scaglioni et al, 2020), and lateral thoracic artery (Ibrahim et al, 2019) are far from the damaged zone and are available in reconstruction. In vessel‐depleted necks, some rarely used recipient vessels, such as the thoracoacromial (Harris et al, 2002) and internal mammary vessels (Urken et al, 2006), have been used.…”
Section: Disscussionmentioning
confidence: 99%